KEY SOURCES OF RESEARCH OF MECHANISMS OF INFORMATION AND COMMUNICATION PROTECTION OF THE SELECTION PROCESS - Mikhailov M.O. (Pressing Problems of Public Administration, 2017)
The author of the article investigates the features of key sources of information and communicationsupport of the electoral process, carrying out the classi cation, de ning the types and types ofsources. Using the achievements of domestic and foreign scholars in this area of activity, the authorreveals the role of sources in the study of the mechanisms of information and communication supportof the electoral process in Ukraine.